2011
DOI: 10.1002/jemt.21048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentin pretreatment with potassium oxalate: Analysis of microtensile bond strengths and morphologic aspects

Abstract: An effective and stable bond is the most desirable characteristic of contemporary adhesive systems. The aim of this study was to evaluate the effect of potassium oxalate on dentin/resin bond strength. Dentin on the occlusal surface of human premolars was exposed and etched with 35% phosphoric acid, to receive 3% monohydrated potassium oxalate and the following adhesive systems: Scotchbond Multipurpose (SMO; 3M/ESPE) and Prime & Bond NT (PBO; Dentsply), followed by the application of resin composite (Z250; 3M/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…De Moraes Porto et al (), using the same methodology of dentin surface treatment, concluded that the bond strength values after storage for 24 h were higher than those observed after 1 year. The application of potassium oxalate on dentin after etching, followed by application of the adhesive does not interfere with adhesive infiltration in a demineralized collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Moraes Porto et al (), using the same methodology of dentin surface treatment, concluded that the bond strength values after storage for 24 h were higher than those observed after 1 year. The application of potassium oxalate on dentin after etching, followed by application of the adhesive does not interfere with adhesive infiltration in a demineralized collagen matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested the use of oxalate for treatment of dentinal sensitivity in 40% of cases (Cunha-Cruz et al, 2010;Pashley & Galloway, 1985;Pereira et al, 2005;Vieira et al, 2009). Furthermore, oxalate-based desensitizing agents are also being studied in laboratory research as an alternative to be added in restorative procedures with the additional effect of improving resin-dentin bonding over time (Cunha-Cruz et al, 2010;De Moraes Porto, De Andrade, Alves, & Braz, 2012). However, the longevity of this bonding must be evaluated in long-term trials.…”
mentioning
confidence: 99%
“…Use of extravagant orthodontic compel may achieve loss of dock and root desorption. In a survey circulated by Katz, an abatement in granulating has been represented by covering the orthodontic wires with inorganic fullerenes-like tungsten disulfi de nanoparticles (IF-WS2) which are known for their astounding oil properties therefore updating the suffi ciency of sliding mechanics (Thompson et al, 2012& De Moraes Porto et al, 2012& Dundar et al, 2011Ouyang et al, 2011.…”
Section: Nanocomposites and Dental Applicationsmentioning
confidence: 99%
“…Some studies have reported that the bond strength to dentin is reduced after treatment with oxalate‐containing desensitizing agents as a result of poor infiltration of the resin caused by the presence of calcium oxalate precipitates in the dentin sub‐surface . On the other hand, other studies , showed that the presence of potassium oxalate crystals did not reduce dentin bond strength and stated that the occlusive potential of oxalates could facilitate the formation of a more stable and homogeneous hybrid layer owing to the obstruction of tubular fluid that could hinder the hydrolytic degradation of the adhesive interface.…”
mentioning
confidence: 99%